The Speech Comprehension Skill Development in Children with ASD of Preschool and Primary School Age - Nikonova N.A; Pavlova U.B (Moscow State University of Psychology and Education, 2018)
Children with autism spectrum disorders frequently have speech problems. Reasons of speech understanding disorders of children are listed. The experience of correction work of teachers on the understanding of the speech and reading in children of the junior, senior preschool and junior school age is described. Presented correctional experience approbated in the school of the Federal Resource Center for the Organization of Comprehensive Support for Children with Autism Spectrum Disorders. The stages of work and methodological recommendations for employment are offered.